Meneguhkan Peran Ayah melalui Tafsir QS. Luqmān:13–18 sebagai Solusi Fenomena Fatherless di Era Modern: Analisis Tafsir Maqāṣidī - Siti Nur Lailatul Azizah; Imroatul Khamidah; Farah Achmanda Kesuma Dianti; Zaenatul Hakamah (Canonia Religia)
The family unit is likened to the smallest ark in society consisting of father, mother, children and other family members. If we look closely, each family member has a role and responsibility in meeting the family's needs. For example, in the position of a father who is the captain of the household, whose duty is to provide support, guidance, direction, protection to his family. Likewise, forgetting the role of a mother who must also act as madrasatul 'ula for her children. Regarding the position of a child, the Qur'an holds that children are the adornment of life and a source of hope for their parents. This research is a library research whose object of study is the phenomenon of fatherlessness and then analyzed using the maqasidi interpretation approach to Jasser Auda's thought style. As a source of primary data, the author uses verses from the Koran which are interpreted through contemporary tafsir books, namely Tafsir Al-Misbah. Meanwhile, as a secondary data source, this research is supported by text books, theses, theses, research journals and internet sources that are still relevant. The data obtained is then analyzed using descriptive analytical content analysis which is useful for finding the main answers to all problems. The results of the analysis that the author obtained are: First, in responding to new phenomena, society should not be fixated on stereotypes from a welfare point of view only. However, they still have to return this phenomenon to the verses of the Koran which are sholih li kulli masa wa makan as a solution for considering a law. Second, a father must be open-minded by opening his views more broadly about cultural stereotypes that are embedded in society and taking part in caring for and educating children. Third, a father must be able to reconstruct his thinking which is not paying enough attention by providing an understanding of causality or the law of cause and effect. It's like if the father only cares about material fulfillment, automatically from the other side the child will make the external environment an object of seeking attention. In this way, it is hoped that fathers can get closer to their children and care more about the child's character growth. So, in terms of theoretical implications, this research can help in designing better educational programs or interventions to increase the role of fathers in forming children's character.